2023
DOI: 10.1038/s41392-023-01464-x
|View full text |Cite
|
Sign up to set email alerts
|

TRP (transient receptor potential) ion channel family: structures, biological functions and therapeutic interventions for diseases

Abstract: Transient receptor potential (TRP) channels are sensors for a variety of cellular and environmental signals. Mammals express a total of 28 different TRP channel proteins, which can be divided into seven subfamilies based on amino acid sequence homology: TRPA (Ankyrin), TRPC (Canonical), TRPM (Melastatin), TRPML (Mucolipin), TRPN (NO-mechano-potential, NOMP), TRPP (Polycystin), TRPV (Vanilloid). They are a class of ion channels found in numerous tissues and cell types and are permeable to a wide range of cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 721 publications
0
22
0
Order By: Relevance
“…Although such an order effect cannot provide an exclusive explanation for such bidirectional changes, it could still be possible that the influence of the experimental order is contaminated. Fourth, it has been widely reported that thermosensitive transient receptor potential (TRP) channels are responsive to heat and/or cold (Caterina et al, 1997; Clapham, 2003; Kashio and Tominaga, 2022; Kauer and Gibson, 2009; Zhang et al, 2023). However, the role of TRP channels in the present study has still been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although such an order effect cannot provide an exclusive explanation for such bidirectional changes, it could still be possible that the influence of the experimental order is contaminated. Fourth, it has been widely reported that thermosensitive transient receptor potential (TRP) channels are responsive to heat and/or cold (Caterina et al, 1997; Clapham, 2003; Kashio and Tominaga, 2022; Kauer and Gibson, 2009; Zhang et al, 2023). However, the role of TRP channels in the present study has still been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TRP melastatin (TRPM), TRP mucolipin (TRPML), TRP polycystin (TRPP), TRPV, and TRP no mechanoreceptor potential (TRPN); the last one is found in fish and invertebrates and not in humans. [62][63][64][65] Increasing numbers of studies provided evidence that many of these proteins are activated by mechanical, physical, and chemical stimuli; their functions are regulated by several mechanisms. TRP channels were first described over 50 years ago.…”
Section: Transient Receptor Potential Channels: Biological Features A...mentioning
confidence: 99%
“…The main roles and functions of different types of TRP channels in both CNS and peripheral nervous system (PNS) and other systems and organs are reported in Table 2. 65 TRP channels are differently expressed in the CNS and PNS of mammals as indicated in Fig. 13.…”
Section: Transient Receptor Potential Channels: Biological Features A...mentioning
confidence: 99%
“…As these channels are involved in pathological processes, including pain and inflammation, TRP channels are considered as promising targets for drug development. 1,2 The main approach has been the inhibition of TRPV (vanilloid) or A (ankyrin), to reduce the progression of the inflammatory pathway or to block pain transduction. Specifically in the case of TRPA, previous studies have shown that its antagonists can effectively alleviate pathophysiological conditions, such as neuropathy of various etiologies and inflammation, with only minor side effects.…”
mentioning
confidence: 99%
“…Transient receptor potential (TRP) channels are a group of nonselective cationic channels expressed in the plasma membrane of a variety of cell types in mammals. As these channels are involved in pathological processes, including pain and inflammation, TRP channels are considered as promising targets for drug development. , The main approach has been the inhibition of TRPV (vanilloid) or A (ankyrin), to reduce the progression of the inflammatory pathway or to block pain transduction. Specifically in the case of TRPA, previous studies have shown that its antagonists can effectively alleviate pathophysiological conditions, such as neuropathy of various etiologies and inflammation, with only minor side effects. Given these clinical implications, efforts have been made to discover new TRPA1 modulators from living organisms.…”
mentioning
confidence: 99%